Pengaruh Antara Kemiskinan dan Investasi Terhadap Ketimpangan - Nurul Huda (Jurnal Ekonomi Manajemen dan Sekretari, 2023)
This study was conducted with the aim of estimating and knowing the results of the analysis of the effect between poverty and investment on inequality in Indonesia in the period 2007 to 2022. The data used is sourced from the Central Statistics Agency (BPS) and the World Bank in Indonesia in the form of Time Series data. This analysis used multiple linear regression and autoregressive distributed lag (ARDL) methods. The results of research with multiple linear regression show that the poverty rate has a negative and insignificant effect on inequality and in the investment sector has a negative and also insignificant effect on inequality in Indonesia. While the results of ARDL in the short and long term that investment has a positive and significant effect on inequality. One of the implications of this finding is an effort to increase investment in order to increase the production of goods and services in a region and can reduce the level of inequality in the region.